PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA KARYAWAN DI PT. POS INDONESIA MEDAN - ERNI WAHYUNI (LP2MTBM MAKARIOZ, 2018)
This research is a primary research with data collection method using questionnaire distributed to employees of PT. Pos Indonesia (Persero) Medan, with random sampling and data analysis using descriptive analysis and statistical analysis. The statistical analysis used in this study is linear regression while the hypothesis test is to use the i test and f test. The results of the discussion show that there is a strong and significant influence between motivation variables (x1) and employee work variables (y). there is also a strong and significant influence between motivation variables (xi) and leadership style (xi) on work motivation (y).From the partial calculation results obtained that the two independent variables namely motivation and leadership style have a significant effect on employee morale at PT. Pos Indonesia (Persero) Medan.The magnitude of the influence of motivation and leadership style on work morale is 82.50% while the remaining 17.50% is influenced by other factors that are not included in the model.